2017
DOI: 10.1001/jamaneurol.2016.6179
|View full text |Cite
|
Sign up to set email alerts
|

Serum C-Reactive Protein as a Prognostic Biomarker in Amyotrophic Lateral Sclerosis

Abstract: IMPORTANCE Various factors have been proposed as possible candidates associated with the prognosis of amyotrophic lateral sclerosis (ALS); however, there is still no consensus on which biomarkers are reliable prognostic factors. C-reactive protein (CRP) is a biomarker of the inflammatory response that shows significant prognostic value for several diseases. OBJECTIVE To examine the prognostic significance of CRP in ALS. DESIGN, SETTING, AND PARTICIPANTS Patients' serum CRP levels were evaluated from January 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
90
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 53 publications
(77 reference statements)
10
90
1
2
Order By: Relevance
“…However, a more recent study by Nagel et al on 289 ALS patients and 506 controls showed a moderate inverse correlation of CRP with ALS-FRSr, which is in concordance with our results [59]. Also in 2017, another study on 394 ALS patients confirmed the CRP-ALS-FRSr correlation [60]. Not only the aforementioned clinical trials but also several other studies support the hypothesis that neuroinflammation is a poor prognostic factor that worsens with disease progression, just as degeneration progresses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, a more recent study by Nagel et al on 289 ALS patients and 506 controls showed a moderate inverse correlation of CRP with ALS-FRSr, which is in concordance with our results [59]. Also in 2017, another study on 394 ALS patients confirmed the CRP-ALS-FRSr correlation [60]. Not only the aforementioned clinical trials but also several other studies support the hypothesis that neuroinflammation is a poor prognostic factor that worsens with disease progression, just as degeneration progresses.…”
Section: Discussionsupporting
confidence: 92%
“…However, these correlations were appropriate for serum CRP concentrations. As suggested previously, CRP in the peripheral blood may be a reflection of the local inflammation in the central nervous system [60]. In our case, only CRP in CSF was negatively correlated with ALS-FRSr (p = 0.009), and no significant correlation was observed in the case of plasma CRP.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, there are no previous reports regarding hs-CRP or GlycA in FTLD or their correlations with the C9orf72 repeat expansion. Lunette and colleagues connected ALS progression with hs-CRP [55], but also inconclusive results have been presented [56]. In the latter study, Nagel et al did not see an association between hs-CRP levels and the risk of ALS.…”
Section: Discussionmentioning
confidence: 97%
“…There is also evidence of increased levels of C reactive protein and erythrocyte sedimentation rate (ESR) in subjects with ALS compared to controls, and evidence that levels correlate with the levels of disability as measured by the ALS functional rating scale (89,(92)(93)(94). Levels of lipopolysaccharide are elevated in patients with ALS, (149), as have levels of nitric oxide, suggesting systemic inflammation (78).…”
Section: Other Evidence Of Systemic Inflammationmentioning
confidence: 99%